Analysis of the Effect of the COVID-19 Pandemic on Syphilis in Susceptible Populations: Men Who Have Sex with Men, People Living with HIV, and Patients with Gestational and Congenital Syphilis—A Narrative Review - Natalia Welc; Wiktoria Frącz; Rafał Olejniczak; Ryszard Żaba; Kevin Kavanagh (Microorganisms, 2025)
The COVID-19 pandemic triggered a public health crisis that significantly impacted sexually transmitted infections (STIs), particularly syphilis. However, data on syphilis incidence during the pandemic remains inconsistent globally. Key groups affected include women of reproductive age, pregnant women, individuals living with HIV, and men who have sex with men (MSM). This paper reviews available literature from databases such as PubMed, Scopus, and Google Scholar to analyse the pandemic’s influence on congenital and gestational syphilis, focusing on high-risk populations. We discuss the pandemic’s impact on the incidence of gestational and congenital syphilis, including changes in screening and treatment protocols. Additionally, we examine alterations in syphilis prevalence and testing among people living with HIV and MSM, including implications observed in blood donors. The findings underscore the consequences of impaired STI diagnostics for public health. We emphasise the need for uninterrupted access to diagnostics and treatment during public health crises. To prevent rising syphilis rates post-pandemic, it is crucial to implement robust education and accessible testing measures.